The effects of remedies on merger activity in oligopoly - Markus Dertwinkel-Kalt; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
We analyze the effects of structural remedies on merger activity in a Cournot oligopoly when the antitrust agency applies a consumer surplus standard. Remedies increase the scope for profitable and acceptable mergers, while divestitures to an entrant firm are most effective in this regard. Remedial divestitures are most attractive from a social welfare point of view, when the merging parties can extract the entire gains associated with the asset sale. We also show that the merging parties have strong incentives to search for the most efficient buyer. Finally, we identify instances so that a remedy rule induces strictly price-decreasing mergers.
Keywords: L13; L41; K21; 330; Remedies; Divestiture; Merger Control; Oligopoly; Synergies